DOI: 10.1007/978-3-540-87603-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Towards Modelling Obligations in Event-B

Abstract: We propose a syntactic extension of Event-B incorporating a limited notion of obligation described by triggers. The trigger of an event is the dual of the guard: when a guard is not true, an event must not occur, whereas when a trigger is true, the event must occur. The obligation imposed by a trigger is interpreted as a constraint on when the other events are permitted. For example, the simplest trigger next, which states that the event must be the next one to be executed when the trigger becomes true, is mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In the various work, different scenarios have been taken into account, from e-Health to Business and Industry. In [30], it is shown that the Event-B language (http://www.event-b.org) can be used to model obliged events. The Rodin platform provides animation and model checking toolset for analyzing specifications written in Event-B, thus leading to capability of obligations analysis [31].…”
Section: Related Workmentioning
confidence: 99%
“…In the various work, different scenarios have been taken into account, from e-Health to Business and Industry. In [30], it is shown that the Event-B language (http://www.event-b.org) can be used to model obliged events. The Rodin platform provides animation and model checking toolset for analyzing specifications written in Event-B, thus leading to capability of obligations analysis [31].…”
Section: Related Workmentioning
confidence: 99%
“…Work in [17] proposes a refined conflict detection technique. In [8], it is shown that the Event-B language (www.event-b.org) can be used to model obliged events. The Rodin platform provides an animation and a model checking toolset for analyzing specifications written in Event-B, thus leading to capability of obligations analysis [4].…”
Section: Related Workmentioning
confidence: 99%
“…Also, the Rodin platform provides animation and model-checking toolset, for developing specifications based on the Event-B language (www.event-b.org). In [17], it is shown that the Event-B language can be used to model obliged events. This could be useful in the case of analysing obligations in DSA.…”
Section: Related Workmentioning
confidence: 99%